Optimizing oral health care for patients in permanent vegetative state: A multidisciplinary approach - Karaboue, Karidia (Progress in Nutrition, 2024)
This article addresses the complex challenges of maintaining oral health in Permanent Vegetative State patients, a demographic often overlooked in dental care due to their unique needs and limitations. Permanent Vegetative State patients, characterized by their lack of consciousness and reliance on artificial feeding methods such as enteral feeding via percutaneous endoscopic gastrostomy, face significant oral health challenges, including increased risk of inflammation, dental and oral trauma, gastroesophageal reflux disease, and complications arising from poor personal oral hygiene. This paper presents a comprehensive oral care protocol tailored specifically for Permanent Vegetative State patients, drawing from practices used for Traumatic Brain Injury  patients. The protocol emphasizes the need for a multidisciplinary approach, integrating the expertise of dentists, speech therapists, and nurses to manage the complex oral health needs of PVS patients effectively. Key components of the protocol include the use of advanced oral hygiene technologies, such as sonic toothbrushes, and strategies to minimize aspiration risks during dental procedures. The protocol also recognizes the psychosocial impact of oral health in PVS patients, highlighting the role of oral care in improving their overall quality of life as perceived by their caregivers. This article aims to shed light on the often-neglected aspect of oral health in PVS patients, proposing a specialized care approach to improve their well-being and facilitate better healthcare outcomes.